The education passport: connecting programmatic assessment across learning and practice - Warm, Eric J; Carraccio , Carol; Kelleher, Matthew; Kinnear, Benjamin; Schumacher, Daniel J; Santen, Sally (Canadian Medical Education Journal, 2022)
Competency-based medical education (CBME) shifts us from static assessment of learning to developmental assessment for learning. However, implementation challenges associated with CBME remain a major hurdle, especially after training and into practice. The full benefit of developmental assessment for learning over time requires collaboration, cooperation, and trust among learners, regulators, and the public that transcends each individual phase. The authors introduce the concept of an “Education Passport” that provides evidence of readiness to travel across the boundaries between undergraduate medical education, graduate medical education, and the expanse of practice. The Education Passport uses programmatic assessment, a process of collecting numerous low stakes assessments from multiple sources over time, judging these data using criterion-referencing, and enhancing this with coaching and competency committees to understand, process, and accelerate growth without end. Information in the Passport is housed on a cloud-based server controlled by the student/physician over the course of training and practice. These data are mapped to various educational frameworks such Entrustable Professional Activities or milestones for ease of longitudinal performance tracking. At each stage of education and practice the student/physician grants Passport access to all entities that can provide data on performance. Database managers use learning analytics to connect and display information over time that are then used by the student/physician, their assigned or chosen coaches, and review committees to maintain or improve performance. Global information is also collected and analyzed to improve the entire system of learning and care. Developing a true continuum that embraces performance and growth will be a long-term adaptive challenge across many organizations and jurisdictions and will require coordination from regulatory and national agencies. An Education Passport could also serve as an organizing tool and will require research and high-value communication strategies to maximize public trust in the work.